Design and synthesis of novel 1, 2-dithiolan-4-yl benzoate derivatives as PTP1B inhibitors. Issue 10 (15th May 2015) - Chen, Jing; Gao, Li-Xin; Gong, Jing-Xu; Jiang, Cheng-Shi; Yao, Li-Gong; Li, Jing-Ya; Li, Jia; Xiao, Wei; Guo, Yue-Wei
Graphical abstract: Abstract: A series of novel 1, 2-dithiolan-4-yl benzoate compounds were synthesized and evaluated for in vitro PTP1B inhibitory activity. Some derivatives exhibited improved PTP1B inhibitory activity and selectivity compared to hit6a, a compound from in-house library screening inspired by marine cyclic disulfide. The preliminary SAR analysis with assistance of molecular modeling approach revealed6j (IC50 = 0.59 μM) as the most potent PTP1B inhibitor among all derivatives.